2013
DOI: 10.1590/s0100-204x2013000600010
|View full text |Cite
|
Sign up to set email alerts
|

Growth and hematology of pacu subjected to sustained swimming and fed different protein levels

Abstract: -The objective of this work was to evaluate the effect of sustained swimming and dietary protein levels on growth and hematological responses of juvenile pacu (Piaractus mesopotamicus). A completely randomized design was used in a 3x2 factorial arrangement, with three levels of dietary protein (24, 28, and 32% crude protein), two rearing conditions (sustained swimming or motionless water), and 15 replicates. Fish were subjected to sustained swimming at the velocity of two body lengths per second (2 BL s -1 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The increase in transaminase activity indicated liver damage. Changes in the content of these enzymes are indications of liver damage caused by an inadequate nutritional balance in the diet, such as excess protein (Nunes et al, 2013), and the effect of anti-nutritional factors or source of the nutrient (Ota et al, 2019). The increase in AST and ALT activities are considered to be a response of the organism to stressors and nutritional metabolism (Meng et al, 2018), which deserves attention because, for this species, longevity is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in transaminase activity indicated liver damage. Changes in the content of these enzymes are indications of liver damage caused by an inadequate nutritional balance in the diet, such as excess protein (Nunes et al, 2013), and the effect of anti-nutritional factors or source of the nutrient (Ota et al, 2019). The increase in AST and ALT activities are considered to be a response of the organism to stressors and nutritional metabolism (Meng et al, 2018), which deserves attention because, for this species, longevity is required.…”
Section: Discussionmentioning
confidence: 99%
“…Proteases are enzymes responsible for the digestion of proteins, from which the AAs are converted to the body mass of the fish. Proteins are the main organic constituents of fish, accounting for from 65 to 75% of the total body dry matter and are associated with fish growth and/or yield (Nunes et al, 2013). The stimulation to produce enzymes by the presence of some specific food is associated with both the production and modulation of genetic expression in the hepatopancreas (Honorato et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Salmo trutta showed the highest rate of weight gain at a water flow rate of 1 BL/s [22]. In addition, some aerobic training also has a positive effect on the growth of non-salmon trout species such as Sparus aurata, Piaractus mesopotamicus and Oreochromis niloticus [23][24][25]. However, there are studies shown that aerobic exercise training has no significant or even negative effects on the growth of fish, such as Oncorhynchus tshawytscha, Procypris rabaudi, Chondwstoma nasus, Paralichthys olivaceus, Xiphophorus montezumae [26][27][28][29][30].…”
Section: Application Of Exercise Training In Aquaculture Speed Up Growthmentioning
confidence: 98%
“…Pacu is valued as a table fish due to its high quality and tasty white meat and as game fish in view of its behaviour in continental sport fishing (David et al 2019a;Furuya et al 2008). Its production has been promoted by its being a rustic, omnivorous species with easy acceptance of formulated feed and intensive systems (David et al 2019a;Nunes et al 2013;Portella et al 2012). This allows production of fish of approximately 1.3 kg in the first 12 months (Urbinati and Gonçalves 2005).…”
Section: Pacu (Piaractus Mesopotamicus)mentioning
confidence: 99%